ECOLOGICAL AND GEOLOGICAL INVESTIGATION OF THE MINE INDUSTRIAL REGIONS IN LUHANSK DISTRICT IN CONNECTION WITH COAL-MINING INDUSTRY’S RESTRUCTURING - Udalov, I.; Chomko, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Goal. A range of problems arisen in the process of coal-mining industry’s restructuring in Luhansk district is analyzed. Methodology. Main factors determining the possibility of unfavorable and dangerous processes related to the closure of coal mines are described and analyzed. The new data of the concentration of heavy metals and toxins in waters, soil, coal waste and rock dumps in industrial areas of closed mines in Luhansk district are obtained. In order to define the pollution level by several elements, a total index of concentration (TIC) has been applied. This index characterizes the overall geochemical load produced by all chemical elements with abnormal level of concentration. Research results. The data processing of lithographic sampling in Luhansk region has helped to define five large and more than 40 smaller areas of anthropogenic pollution. Within the main industrial areas, the more intensely polluted sites (2-32 km2) were revealed. They are related to some plants or industrial units. TIC here is 16-50, and in some sites it reaches 150. Topicality. It is revealed that the most contrasting (TIC 8 – 126) and extensive (410 km2) anthropogenic area is located in Almazno-Mar`yvsk mine industrial region and stretches over 48 km in the northwest direction from the town of Perevalsk to the town of Zolotoye. Typical contaminants for this region are arsenic, lead, fluorine, mercury, barium, manganese. Within the region, large areas (15-25 km2) with the maximum (TIC 16-77) pollution level of land were revealed. They are limited to industrial and intended for building landscapes of the towns of Alchevsk, Bryanka, and Stahanov. More local (1-4 km2) but nevertheless more contrasting (TIC 16-126) abnormalities related to contamination are recorded near the coil mining plants of the towns of Teplohorsk, Zolotoye, and Horskoye. Conclusion. The main pollutants of soils and bed deposits are revealed, they are the following: arsenic, lead, fluorine, mercury, phosphorus, zinc, and barium. Cadmium, thallium, antimony, manganese, lithium, copper and chromium are also found. In order to determine the level of land pollution by several elements, the total index of concentration was used. The specific features related to the occurrence of some microelements in industrial waste of Donbas are described, their probable sources and possible ways of use are suggested.